Green function for the problem of sound radiation by a circular sound source located near two-wall corner and three-wall corner - Rdzanek, W.J.; Rdzanek, W.P. (Archives of Acoustics, 2006)
The construction of the Green functions for the Neumann boundary value problems of the Helmholtz equation at the two-wall corner and the three-wall corner has been described. The Green functions have been expressed in their Fourier representation and have been used for computations of the radiation sound pressure of a flat circular source located in one of the two rigid baffles of the two-wall corner and in one of the three rigid baffles of the three-wall corner.